Antioxidant Activity of Extracts from Bidens pilosa-A Medicinal Plant from the Kingdom of Lesotho - Manoharan Karuppiah Pillai; Keketso, Mahase; Rets'epile Paul Matamane (Fine Chemical Engineering, 2023)
Bidens pilosa finds therapeutic applications in the traditional medicine. In the present study, we aimed to evaluate the antioxidant activity of various extracts obtained from the leaves and stem-bark of B. pilosa by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and ferric reducing power assay. We also aimed to determine the total phenolic contents (TPCs) by Folin-Ciocalteu colorimetric method and total flavonoid contents (TFCs) by the aluminium chloride colorimetric method. Various solvent extracts were obtained from the leaves and stem-bark of B. pilosa by maceration and hot solvent extraction techniques. The extracts from leaves and stem-bark exhibited radical scavenging activity in the ranges of 4.40 ± 1.02-81.18 ± 1.14% and 5.92 ± 2.16-79.34 ± 8.43%, respectively at concentrations of 200-3,000 µg/mL. The positive control, ascorbic acid exhibited radical scavenging activity in a range of 55.17 ±1.89-88.12 ± 1.31% at the same concentrations. Additionally, the methanol extracts from both leaves and stem-bark were found to be the most potent with IC50 values of 848.54 and < 200 µg/mL, respectively. The positive control, ascorbic acid exhibited an IC50 value < 200 µg/mL. Furthermore, the extracts from the leaves and stem-bark exhibited ferric reducing power in the ranges of 0.095 ± 0.017-1.175 ± 0.084 and 0.093 ± 0.006-1.100 ± 0.065, respectively at concentrations of 5-100 µg/mL. The positive control, ascorbic acid exhibited a ferric reducing power in the range of 0.326 ± 0.00-1.213 ± 0.078 at concentrations of 5-100 µg/mL. In addition, the TPCs of extracts from the leaves and stem-bark were determined to be in the ranges of 9.03 ± 2.34-179.31 ± 0.96 and 10.93 ± 1.04-154.04 ± 2.15 mg GAE/g of DW of extract, respectively. Similarly, the TFCs of extracts from the leaves and stem-bark were determined to be in the ranges 1.28 ± 0.05-29.33 ± 4.19 and 1.89 ± 0.58-27.75 ± 2.67 mg QE/g of DW of extract, respectively. From this study, we concluded that various extracts obtained from B. pilosa showed a moderate to strong radical scavenging and ferric reducing power and possessed a significant amount of TPCs and TFCs.